INDUSTRIALIZATION IN THE FACE OF RECESSION: THE NIGERIAN EXPERIENCE - Odey, Stephen Adi (Advances in Social Sciences Research Journal, 2018)
Industrialization, it is believed comes with some level of improvement in the standard of living, since it tends to make more readily available social amenities and infrastructure through which the ever-changing needs and challenges of the society are addressed. There are factors necessary for appreciable rate of industrialization to be achieved including some level of security, significant sufficiency in agricultural productivity, adequate fuel and raw materials supply, effective transport and communication system, adequate human capital, stable and supportive financial services sector, consistency in government policy and effective and functioning government institutions. Economic recession which is seen as a widespread and consistent reduction in productive activity, over a number of months resulting in a fall in gross domestic product and income per capita as well as increased unemployment levels and a general shrinking of the economy comes with the absence of one of the most vital requirements for industrialization, namely increased cash injection for investing in capital projects and industrial development. Successive Nigerian government administrations have paid lip service to industrial development and the current recession makes industrialization more challenging especially because of high inflation, dwindling purchasing power and general shrinking of the economy. Some the most critical challenges are hardly available power supply, corruption, unfavourable exchange rates and highly porous borders. It is recommended that government finds the political will and courage to resolve the identified challenges towards returning Nigeria to the path of industrial development.